Next-Gen Firewalls and Network Security: Enhancing Defense through Advanced Threat Mitigation Techniques - Srikanth Bellamkonda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Next-generation firewalls (NGFWs) are becoming essential in defending against increasingly sophisticated cyber threats. This comprehensive article explores the evolution of network security architecture, focusing on the transformative role of NGFWs in modern defense strategies. The article examines core components, including deep packet inspection, application awareness, and integrated threat intelligence, while evaluating advanced threat mitigation techniques and implementation strategies. The article highlights how organizations can optimize their security infrastructure by assessing performance considerations and scalability requirements. Furthermore, the article investigates emerging technologies and integration capabilities shaping network security’s future, demonstrating how NGFWs enhance organizational resilience against evolving cyber threats through improved detection, prevention, and response capabilities.